2002
DOI: 10.1103/physrevb.65.104404
|View full text |Cite
|
Sign up to set email alerts
|

Pressure effect on the magnetism of layered copper(II) compounds with interlayer spacing up to 40.7 Å: Nature of the magnetic ordering

Abstract: The influence of pressure on the structure and magnetic properties of the layered hybrid compounds Cu 2 (OH) 3 (n-C m H 2mϩ1 CO 2 )•zH 2 O is investigated for mϭ10 and 12. It is shown that the distance between magnetic copper͑II͒ layers, up to 40.7 Å, is not significantly modified and that the temperature of the ferromagnetic ordering decreases linearly with pressure increase. We present a new analysis of the susceptibility data, based on the scaling theory of phase transitions, which clearly shows up a crosso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 19 publications
2
55
0
Order By: Relevance
“…This minimum is well fitted by the superposition of two exponentials: a high-temperature AF contribution which vanishes at absolute zero, and a low temperature ferromagnetic one, describing the strong variation in the temperature range 50±300 K. Note that the latter is fully justified for a 2D Heisenberg ferromagnet, whose low-temperature behavior is given by vT = exp(4pJS 2 /kT) [86] where J is the in-plane exchange constant. Therefore, the data have been fitted with the expression: [87] vT = C 1 exp(aJ/kT) + C 2 exp(bJ/kT)…”
Section: Influence Of Organic Spacersmentioning
confidence: 99%
See 2 more Smart Citations
“…This minimum is well fitted by the superposition of two exponentials: a high-temperature AF contribution which vanishes at absolute zero, and a low temperature ferromagnetic one, describing the strong variation in the temperature range 50±300 K. Note that the latter is fully justified for a 2D Heisenberg ferromagnet, whose low-temperature behavior is given by vT = exp(4pJS 2 /kT) [86] where J is the in-plane exchange constant. Therefore, the data have been fitted with the expression: [87] vT = C 1 exp(aJ/kT) + C 2 exp(bJ/kT)…”
Section: Influence Of Organic Spacersmentioning
confidence: 99%
“…here the behavior of the copper(II) hydroxide-based compounds in the framework of the scaling theory of phase transitions. [92] This theory assumes that length of the spin correlations diverges like n = n 0 (1-T c /T) ±c , wherefrom it follows that the vT product may be written as: [87] vT = C (1-T c /T) ±c = C(1-T c /T) ±h/Tc with h = cT c where C is the high temperature Curie constant. Near T c , when n diverges, the exponent c takes universal values which only depend on the spin and space dimensions.…”
Section: Origin Of the Phase Transitionmentioning
confidence: 99%
See 1 more Smart Citation
“…To rationalize this evolution, Equation 2 is used to describe the magnetic behavior. [18] xT ¼ C 1 expðaJ=k B TÞ þ C 2 expðbJ=k B TÞ…”
mentioning
confidence: 99%
“…On the other hand, interesting studies have been performed on 2D systems with different intraand interlayer magnetic interactions. 2,3 Previous studies by Kahn and co-workers in designing molecule-based magnets have shown that organizing ferromagnetic arrangements in extended 2D or 3D systems is quite a difficult task. 1 The choice of a specifically tailored building block is crucial in the design of systems with tunable dimensionality displaying ferromagnetic coupling.…”
mentioning
confidence: 99%